(untitled) (Bangladesh Journal of Nuclear Medicine, 2016)
Thyroid hormones play a critical role in the adult brain impacting mood and cognition. Some psychiatric symptoms are produced by thyroid illnesses and there is a frequent association of thyroid dysfunction with mood disorders. It is now clear that without optimal thyroid function, mood disturbance, cognitive impairment and other phychiatric symptoms can emerge. The usefulness of adding thyroid hormones to antidepressive treatment in euthyroid patients to obtain a potentiation effect has been proved repeatedly. The most common strategy is potentiation with T3 , but high doses of T4 have been also used in patients with resistant depression. Brain imaging techniques evaluating cerebral metabolism, perfusion, and anatomy enabled encouraging insights into the thyroid-brain relationship. The most consistent finding in patients with hypothyroidism is global diffuse hypoperfusion more pronounced in posterior brain region or in parietal lobe. Functional MRI in patients with thyroid diseases of different length and severity could help to identify functional aberrations such as memory impairments or altered emotional processing, which has long been suggested from animal studies. Structural changes related to myelin, which have been observed in various animal models, can now be studied with quantitative T2 or quantitative magnetization transfer (MT) imaging. Diffusion tensor imaging (DTI) can reveal information on white matter integrity. Bangladesh J. Nuclear Med. 17(2): 146-152, July 2014